1997
DOI: 10.1143/jjap.36.3233
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Trabecular Structure on Ultrasonic Wave Propagation in Bovine Cancellous Bone

Abstract: Ultrasonic wave propagation in water-saturated bovine cancellous (spongy) bone has been experimentally studied in vitro by a pulse transmission technique. The propagation of fast and slow longitudinal waves in bovine cancellous bone [rf:1] is examined in relation to porosity using Biot's and Wyllie's equations to estimate the measured speeds versus porosity. In the high porosity range, the trabecular structure influences the propagation of the fast and slow waves in cancellous bone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
47
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 10 publications
4
47
0
Order By: Relevance
“…It has been shown that both fast and slow longitudinal waves propagate through trabecular bone as predicted by Biot's theory and that experimentally observed propagation speeds for fast and slow waves coincided well with the theoretically calculated ones [12][13][14]. The propagation speeds and amplitudes of the fast and slow waves are significantly affected by the trabecular micro-and macro-structures, the trabecular orientation to the propagation direction, and the visco-elastic properties of bone marrow [12][13][14][15].…”
Section: Introductionsupporting
confidence: 57%
See 2 more Smart Citations
“…It has been shown that both fast and slow longitudinal waves propagate through trabecular bone as predicted by Biot's theory and that experimentally observed propagation speeds for fast and slow waves coincided well with the theoretically calculated ones [12][13][14]. The propagation speeds and amplitudes of the fast and slow waves are significantly affected by the trabecular micro-and macro-structures, the trabecular orientation to the propagation direction, and the visco-elastic properties of bone marrow [12][13][14][15].…”
Section: Introductionsupporting
confidence: 57%
“…According to the Biot's theory, the fast wave is related to a propagation mode mainly involving the solid phase (trabecular network), whereas the slow wave is related to the fluid phase (bone marrow), and the arrival time of the fast wave is simply determined by the speed and the distance of propagation in bone tissue [19]. It has been shown that both fast and slow longitudinal waves propagate through trabecular bone as predicted by Biot's theory and that experimentally observed propagation speeds for fast and slow waves coincided well with the theoretically calculated ones [12][13][14]. The propagation speeds and amplitudes of the fast and slow waves are significantly affected by the trabecular micro-and macro-structures, the trabecular orientation to the propagation direction, and the visco-elastic properties of bone marrow [12][13][14][15].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Because the fast wave mainly propagates in the solid trabecular frame, the wave properties reflect the state of the cancellous structure of the bone. [14][15][16] In addition, Otani has reported a good relation between the slow wave amplitude and bone volume and introduced a new bone densitometry apparatus for clinical studies. The apparatus can give us data which have a high correlation with bone mineral density by peripheral quantitative computed tomography.…”
Section: Introductionmentioning
confidence: 99%
“…In previous research for experimental observations of the ultrasonic wave propagation in bovine cancellous bone [3][4][5], it was shown that cancellous bone had a strong acoustic anisotropy depending on the trabecular structure. Both the fast and slow longitudinal waves, which are predicted in Biot's theory [6,7], could be clearly observed in the direction parallel to the trabecular alignment, whereas a single wave could be observed in the perpendicular direction.…”
Section: Introductionmentioning
confidence: 99%